Smilisca phaeota (Cope, 1862) (Anura: Hylidae) tadpoles do not discriminate between siblings and non-siblings (2006)
ABSTRACT: Kin recognition behavior (based on the spatial affinity for siblings index [S]) was examined in Smilisca phaeota tadpoles injected with odorific substances (experimental tadpoles). According to the S index values obtained, these tadpoles did not discriminate between relatives and nonrelatives when they were presented with unfamiliar sibling and non-sibling individuals. Since these results were similar to those obtained from control tadpoles(not exposed to odorific substances), I conclude that this species does not exhibit kin recognition behavior. Ecological factors such as the predation risks to tadpoles in the puddles where they live and their behavior are discussed as possible explanations for the results presented here.